2017
DOI: 10.1016/j.jenvp.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in values determine the relative persuasiveness of biospheric, economic and combined appeals

Abstract: Many environmental campaigns highlight both the environmental and financial benefits of behaviour change, in the hope of motivating a broad audience. But are such mixed appeals more persuasive than separate appeals? We argue that messages tailored to match recipient's prioritised values are more persuasive than combined appeals. We conducted a questionnaire study to assess the persuasiveness of economic, environmental, and mixed appeals (N ¼ 210). As expected, individual differences in values moderated the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 43 publications
2
54
1
1
Order By: Relevance
“…Studies have also demonstrated that extrinsic motivation negatively affects PEB. For example, extrinsic rewards reduced the motivation to engage in energy-saving programs (Schwartz, Bruine de Bruin, Fischhoff, & Lave, 2015) and using financial gains as a motivator is detrimental to holding attention to those with pro-environmental values (van den Broek, Bolderdijk, & Steg, 2017).…”
Section: Self-determination Theory and Crowding Outmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also demonstrated that extrinsic motivation negatively affects PEB. For example, extrinsic rewards reduced the motivation to engage in energy-saving programs (Schwartz, Bruine de Bruin, Fischhoff, & Lave, 2015) and using financial gains as a motivator is detrimental to holding attention to those with pro-environmental values (van den Broek, Bolderdijk, & Steg, 2017).…”
Section: Self-determination Theory and Crowding Outmentioning
confidence: 99%
“…The shortened version of the revised New Environmental Paradigm (NEP) scale (Dunlap, Van Liere, Mertig, & Jones, 2000;Whitmarsh & O'Neill, 2010) was used as a proxy for autonomous environmental motivation (e.g., van den Broek et al, 2017). Environmental beliefs have been demonstrated to correlate significantly with environmental motivation, with stronger positive correlations for more selfdetermined motives (most strongly with intrinsic) and weaker and negative correlations with less self-determined motivation (e.g., Pelletier et al, 1998).…”
Section: Autonomous Environmental Motivationmentioning
confidence: 99%
“…However, companies should avoid overemphasizing pecuniary motivations to the exclusion of moral concerns, because financial concerns should be less value congruent for low Machiavellians and may actually decrease their motivation for honest sustainability reporting (cf. van den Broek et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological studies suggest that educational interventions should be congruent with the values of target groups to be persuasive (Bashir, Lockwood, Dolderman, Sarkissian, & Quick, 2011;Bolderdijk, Corsira, Keizer, & Steg, 2013;Jost, Frederico, & Napier, 2009;van den Broek, Bolderdijk, & Steg, 2017). For instance, van den Broek et al (2017) found that educational campaign messages that emphasize the financial benefits of environmentally conscious behaviours were more effective for individuals with egoistic values, while an emphasis on protection of the environment was more effective for those with stronger biospheric values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation